(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Academic resilience indicates a higher possibility of success in academic settings despite difficulties. It is reported that India has seen a rise in dropout rates, disengagement from educational institutions, and suicidal tendencies among students over the last decade. Students are becoming less resilient in dealing with academic stress which negatively affects their overall wellbeing. Thus, academic resilience can assist a student to bounce back from various academic adversities. A systematic narrative review was conducted to gain an in-depth understanding of the current state of knowledge about academic resilience in India. Between June 2022 and August 2022, three databases – Scopus, Dimensions AI, ERIC, and other sources like Google Scholar and Shodhganga were searched systematically. The systematic literature search identified 2645 records, of which 17 studies were eligible as per the criteria laid down in this study. The findings of this review have highlighted different methodologies employed for assessing academic resilience, and various individual and environmental protective factors which promote academic resilience. This review will help researchers, educators, and other stakeholders of education in India to comprehend the concept of academic resilience and provide guidance on developing effective intervention programmes to foster academic resilience among students.